Respuesta :

Answer:

The solution of the given equation is

[tex]x = \frac{9}{1-e^{3} }[/tex]

Step-by-step explanation:

Given Log(x+9) - log x =3

By using Formula  log a -log b = log(a/b)

[tex]log (\frac{x+9}{x} ) = 3[/tex]  ...(i)

we apply another logarithmic formula

[tex]log^{x} _{e} = y[/tex]   then    x  = [tex]e^{y}[/tex]

Now From (i) we get

[tex]\frac{x+9}{x} = e^{3}[/tex]

On cross multiplication , we get

x +9 = e³ x

x +9 -e³x =0

x (1 - e³) = -9

[tex]x = \frac{-9}{1-e^{3} } = \frac{9}{1-e^{3} }[/tex]

Final answer:-

The solution of the given equation is

[tex]x = \frac{9}{1-e^{3} }[/tex]

Answer:

decimal form X=0.009

exact form x=1/100

Step-by-step explanation: